2021
DOI: 10.3847/1538-4357/abf247
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Stellar Ca ii H and K Emission Variations. I. Effect of Inclination on the S-index

Abstract: The emission in the near-ultraviolet Ca ii H and K lines is modulated by stellar magnetic activity. Although this emission, quantified via the S-index, has been serving as a prime proxy of stellar magnetic activity for several decades, many aspects of the complex relation between stellar magnetism and Ca ii H and K emission are still unclear. The amount of measured Ca ii H and K emission is suspected to be affected not only by the stellar intrinsic properties but also by the inclination angle of the stellar ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Previous studies indicated that such a transition can be reproduced by extrapolating the observed dependencies of solar facular and spot area coverage on the S-index (Shapiro et al 2014). Instead of relying on these extrapolations, which are purely empirical and assume that any trend seen on the Sun continues unchanged to more active stars, we combined our calculations of spot and facular coverages with models of stellar photometric brightness from N20 and Ca II H&K emission developed by Sowmya et al (2021). Namely, we used the model introduced in N20 to calculate the activity-induced alteration in Strömgren (b+y)/2, (b + y)/2 quiet − (b + y)/2 active , where the first term represents the brightness of a star free from any magnetic features and the second term quantifies the brightness in the presence of magnetic activity (so that a positive alteration of Strömgren (b+y)/2 corresponds to an overall brightening with increasing magnetic activity, while a negative alteration corresponds to a dimming).…”
Section: Active Starsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that such a transition can be reproduced by extrapolating the observed dependencies of solar facular and spot area coverage on the S-index (Shapiro et al 2014). Instead of relying on these extrapolations, which are purely empirical and assume that any trend seen on the Sun continues unchanged to more active stars, we combined our calculations of spot and facular coverages with models of stellar photometric brightness from N20 and Ca II H&K emission developed by Sowmya et al (2021). Namely, we used the model introduced in N20 to calculate the activity-induced alteration in Strömgren (b+y)/2, (b + y)/2 quiet − (b + y)/2 active , where the first term represents the brightness of a star free from any magnetic features and the second term quantifies the brightness in the presence of magnetic activity (so that a positive alteration of Strömgren (b+y)/2 corresponds to an overall brightening with increasing magnetic activity, while a negative alteration corresponds to a dimming).…”
Section: Active Starsmentioning
confidence: 99%
“…These calculations have been performed for the daily snapshots of the disc distributions of magnetic features for all activity levels (s) used in this study (see Fig 1b,c). Then we used the Sowmya et al (2021) model for the Ca II H&K emission to calculate the corresponding S-index values. As a result, we obtained a contemporaneous time series of Strömgren (b+y)/2 and the S-index, by combining all five modelled activity levels into a 55-year time series.…”
Section: Active Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…This index serves as a reference standard for the strength of a star's magnetic activity, thus facilitating a direct comparison with the Sun (Baliunas et al 1995; Duncan et al 1991; Hall 1996; Schröder et al 2018). Sowmya et al (2021) pursued a different approach using synthesized Ca ii H & K spectra to calculate a realistic solar S ‐index, which was validated with solar Ca ii H & K imaging and spectral data, to assess stellar magnetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…This index serves as a reference standard for the strength of a star's magnetic activity, thus facilitating a direct comparison with the Sun (Baliunas et al, 1995;Duncan et al, 1991;Hall, 1996;Schröder, Schmitt, Mittag, Gómez Trejo, & Jack, 2018). Sowmya et al (2021) pursued a different approach using synthesized Ca ii H & K spectra to calculate a realistic solar S-index, which was validated with solar Ca ii H & K imaging and spectral data, to assess stellar magnetic activity.…”
Section: Introductionmentioning
confidence: 99%